INTERVENSI MULLIGAN BENT LEG RAISE EXERCISE LEBIH BAIK DARI PADA MC. KENZIE EXTENSION EXERCISEDALAM MENURUNKANNYERI DAN DISABILITAS PADA KASUS NYERI PINGGANG MIOGENIK DI RS.BAYUKARTA (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2017)
AbstractObject : to prove Mulligan bent leg raise is better than  Mc. Kenzie extension exercise  to reduce pain and disability in miogenik low back pain. Methods : experimental. Sampel are 10 employers at Bayukarta hospital. Choosen by purposive sampling.Results : after 12 times exercise. Hypothesis I using  paired sample t-test obtained VAS average before (58.40±3.91) and after (35.00±5.61) then p =0.001 and ODI average  before (38.80±2.28)  and after (21.00±8.94) then p =0.006 which means Mulligan bent leg raise can reduce pain and disability. Hypothesis II using paired sample t-test obtained VAS value before (57.20±7.62) and after (37.60±8.20) then p< 0.001  and ODI using Wilcoxon test, average before (44.80±5.01) and after (30.80±8.43) then  p=0.042 which means Mc. Kenzie extension exercise can reduce pain and disability. On hypothesis III using Mann Whitney u-test  obtained ODI average difference of one (21.00±8.94) and two (30.80±8.43) then  p = 0.249  and VAS using independent t-test obtained after one (58.40±3.91) and two  (57.20 ±7.62)  p=0.575 which meaning  Mulligan bent leg raise is not better than  Mc. Kenzie extension exercise. Conclution: Mulligan bent leg raise is not better than  Mc. Kenzie extension exercise to reduce pain and disability in miogenik low back pain at Rs. Bayukarta.                  Keywords : Mulligan bent leg raise exercise, Mc. Kenzie extension exercise, pain, disability.AbstrakTujuan :Untuk membuktikan intervensi Mulligan bent leg raise exercise lebih baik dari pada Mc. Kenzie extension exercisedalam menurunkannyeri dan disabilitaspada nyeri pinggangmiogenik. Metode :eksperimental.10 sampel pegawaidi RS.Bayukarta,tekniknyapurposive sampling.Hasil : setelah 12 kali latihan. Hipotesis I menggunakanpaired sample t-test, VAS rerata sebelum (58.40±3.91) dan sesudah (35.00±5.61)maka p=0.001danODI rerata sebelum (38.80±2.28)dan sesudah (21.00±8.94) maka p=0.006berartiintervensiMulligan bentlegraisedapatmenurunkannyeridandisabilitas. Hipotesis II menggunakanpaired sample t-testdanWilcoxon testdidapatkanVAS rerata sebelum (57.20±7.62) dan sesudah (37.60±8.20)maka p<0.001dan ODI rerata sebelum (44.80±5.01)dan sesudah (30.80±8.43) makap= 0.042 berartiintervensiMc. Kenzie extension exercisedapatmenurunkannyeridandisabilitas. Hipotesis III menggunakanMann Whitneyu-test,ODI rerata selisih 1 (21.00±8.94) dan 2 (30.80±8.43) maka p=0.249dan VAS menggunakanindependen t-test didapat rerata sesudah 1 (58.40±3.91) dan 2 (57.20 ±7.62) maka  p=0.575 yang berartiintervensiMulligan bentlegraisetidak lebihbaikdaripadaMc. Kenzie extension exercisedalammenurunkannyeridandisabilitas. Kesimpulan :IntervensiMulligan bentlegraisesama baiknya denganMc. Kenzie extension exercise dalam menurunkan nyeri dan disabilitas pada kasus nyeri pinggang miogenik di Rs.Bayukarta. Kata Kunci :Mulligan bent leg raise exercise, Mc. Kenzie extension exercise,nyeri, disabilitas.